Repurposing of Yunnan Baiyao as an Alternative Therapy for Minor Recurrent Aphthous Stomatitis. (4th December 2012) - Liu, Xiaosong; Guan, Xiaobing; Chen, Ruiyang; Hua, Hong; Liu, Yang; Yan, Zhimin
Abstract : The study was designed to evaluate the efficacy and safety of an herbal extract of Yunnan Baiyao formulated in toothpaste as an alternative therapy for minor RAS. A randomized, double-blind, placebo-controlled clinical trial (from March 2010 to March 2011) was conducted on a cohort of 227 minor RAS patients. The toothpaste containing Yunnan Baiyao was used twice daily as part of the patient's routine oral hygiene for 5 days. An assessment of ulcerative size and pain was recorded on day 0 (baseline), day 3, and day 5. Any noted adverse reactions were recorded. All data were analyzed using the SAS software 8.0. As a result, the toothpaste containing Yunnan Baiyao began to present noticeable effectiveness on ulcer healing (ulcer size) by day 3 (27.5% versus 15.8%, P < 0.05 ), which further improved by day 5 when compared to the placebo (66.4% versus 50.0%, P = 0.01 ). A significant difference in alleviating pain was noted on day 5 for those who used the toothpaste containing Yunnan Baiyao (66.4% versus 51.8%, P < 0.05 ). No side effects were noted as a result of the Yunnan Baiyao. Therefore, Yunnan Baiyao may provide an alternative therapy for minor ulcers by promoting healing.